The Modsuung Davason community ritual, Kimanis sub-district, Papar, Sabah - Dunstan Oswald Roland; Jacqueline Pugh-kitingan; Trixie Marjorie Tangit (Borneo Research Council, Inc, 2024)
The Modsuugn Davason (offereings at the river mouth) of the Kadazan community of Kimanis, originated from the Makan Kuala (food for the river mouth) of the coastal Brunei community, and was performed for the socio-economic well-being and protection of the different ethnic communities in Kimanis, Papar. Based on ethnographic fieldwork from 2014 to 2018, this article describes the ritual process of the annual Modsuung Davason that also included Berasik healing ceremonies every three years. Offerings were prepared by Kadazan bobohizan priestesses, placed into an 'ajung' or small boat for the spirits, and towed by two conjoined larger boats accompanied by many other boats down the Kimanis River. At the river mouth, most of the offerings were placed in a ritual house for the spirits, while the ajung with the remaining offerings was towed out to sea. The last Modsuung Davason was held in 2019. It became obsolete with he passing of ritual specialists and the COVID-19 pandemic. For many people, the pandemic demonstrated the inefficacy of the old rituals and the powerlessness of the spirits to protect the communities.